Thermal characterisation of binary sodium/lithium nitrate salts for latent heat storage at medium temperatures - Dan Zhou; Philip Eames (2016)
Latent heat storage in molten salt mixtures has been considered as a promising method for medium temperature solar thermal storage and industrial waste heat storage. The binary sodium/lithium nitrate salt mixture is one of the potential candidate materials. However there is limited information on their thermal performance except for their phase diagrams. In this paper, two binary salts, NaNO3–LiNO3 (46–54%) and NaNO3–LiNO3 (40–60%), were investigated to assess their suitability for medium temperature heat storage. The thermal properties and long term stability under multiple cycles of each binary salt pair were investigated using Differential Scanning Calorimetry (DSC). The chemical stability at elevated temperatures was tested using a Thermogravimetric Analyser (TGA). Both binary salts analysed have suitable melting temperatures (just under 200 °C) with relatively high latent heat values (>220 kJ/kg), both exhibiting good thermal and chemical stability.